Assistance in preparing teaching modules containing literacy and numeracy for the art and culture MGMP of Semarang Regency Middle School - Salafiyah, Nafik; Sejati , Irfanda Rizki Harmono; Aesijah, Siti; Susetyo, Bagus; Pradana , Reksada Belly (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Since 2022, the Merdeka Curriculum has incorporated literacy and numeracy into arts and culture education. However, a major challenge faced by arts and culture teachers is that not all of them fully understand or have mastered how to integrate literacy and numeracy into their teaching, particularly in the development of existing teaching modules. The purpose of this community service initiative is to provide mentoring in developing teaching modules that integrate literacy and numeracy into the subjects of music, dance, and visual arts for the Arts and Culture Teachers’ Working Group (MGMP). The method used in this program involved several stages: beginning with the dissemination and introduction of key concepts, followed by practical assistance in developing literacy- and numeracy-based teaching modules, and concluding with simulations to support the practical implementation of learning. The results of this initiative show that the development of literacy and numeracy skills can be facilitated through theoretical and practical learning materials, differentiated and contextual methods, educational field trips, various learning media and tools (both digital and conventional), as well as through the use of effective teaching models, strategies, and assessment techniques. The benefits of this program include improved teacher understanding of literacy and numeracy, enhanced teacher competence in module development, increased creativity in delivering learning materials, the establishment of collaborative and professional learning environments, and the successful creation of arts and culture teaching modules that incorporate literacy and numeracy. Based on these outcomes, it can be concluded that the development of integrated literacy and numeracy teaching modules for music, dance, and visual arts subjects in the MGMP for arts and culture has provided significant and valuable benefits.